2022
DOI: 10.3389/fimmu.2022.996875
|View full text |Cite
|
Sign up to set email alerts
|

Increased monocyte abundance as a marker for relapse after discontinuation of biologics in inflammatory bowel disease with deep remission

Abstract: Monocytes are involved in the upstream inflammatory process in the immune reaction in inflammatory bowel disease (IBD). Patients with IBD who discontinued biologics have been found to relapse, even after checking for deep remission. This study investigated whether monocytes could act as a predictor of relapse in patients who experienced relapse after the discontinuation of biologics. To this end, pediatric patients (<19 years old, n = 727) diagnosed with IBD from January 2003 to December 2021 were retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Basophils and monocytes have been implicated in IBD in human samples, as assessed by the presence of monocyte chemotactic protein-3 expression, an activator of basophils and monocytes, in sites of active mucosal inflammation [ 85 ]. Interestingly, an increased concentration of monocytes is associated with a high degree of probability of relapse of IBD in patients during remission [ 86 ]. LoCHO_PROT, but not LoCHO_FAT, significantly reduced concentrations of IL-8 and IL-33, and both inflammatory markers are associated with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Basophils and monocytes have been implicated in IBD in human samples, as assessed by the presence of monocyte chemotactic protein-3 expression, an activator of basophils and monocytes, in sites of active mucosal inflammation [ 85 ]. Interestingly, an increased concentration of monocytes is associated with a high degree of probability of relapse of IBD in patients during remission [ 86 ]. LoCHO_PROT, but not LoCHO_FAT, significantly reduced concentrations of IL-8 and IL-33, and both inflammatory markers are associated with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the proportion of classical monocytes in the peripheral blood of patients with UC is reduced during inflammatory activity, suggesting that these cells may migrate to the intestine and promote inflammatory processes [ 9 , 10 ]. Monocytes are involved in the upstream inflammatory process of the immune response to IBD, and patients with high monocyte counts experience a recurrence of inflammation after discontinuation of biologics [ 22 ]. TIM4-expressing monocytes are novel indicators of the disease activity and severity of UC; CD14 TIM4 cells were reported to be elevated in patients with UC, and the percentage of TIM4-expressing monocytes was significantly lower in such patients treated with mesalazine [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results show a decrease in all subsets of monocytes in Crohn's patients, including an expression of CD163 and CCR2. An overview of a cohort of IBD patients over 19 years shows they were able to demonstrate high monocyte counts, which shows these patients may be more likely to experience relapses [40] . The non-classical monocytes, on the other hand, show an increase in chemokine receptors in Crohn's patients.…”
Section: Discussionmentioning
confidence: 99%